Hydrogen isotopes retention studies using laser and microwave induced plasma coupling - N. Vujadinovic; I. Traparic; B. D. Stankov; D. Rankovic; M. Kuzmanovic; M. Ivkovic (Scientific Reports)
Abstract The detection of deuterium and tritium retention in fusion devices via optical emission spectroscopy (OES) faces significant challenges due to experimental limitations, particularly in resolving hydrogen isotope Balmer alpha lines (Hα, Dα, and Tα). In this study, we propose and evaluate the coupling of laser ablation and laser-induced desorption with microwave-induced plasma (MIP) as an approach to resolve this problem. This approach effectively meets the resolution requirements for Balmer alpha lines, overcoming limitations of standard laser-induced breakdown spectroscopy (LIBS) setups. Optimization of Nd:YAG laser ablation was performed using pure copper and tungsten targets, while desorption, including femtosecond (fs) laser-induced desorption, was studied on graphite powder mixed with heavy water and water. The results demonstrate a significant improvement in spectral resolution and analytical performances, highlighting the potential of this technique for tritium retention studies in plasma-facing components.